2019
DOI: 10.1182/blood-2019-121584
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Transcriptome Analysis Reveals Disease-Defining T Cell Subsets in the Tumor Microenvironment of Classic Hodgkin Lymphoma

Abstract: INTRODUCTION: Classic Hodgkin lymphoma (cHL) is uniquely characterized by an extensively dominant microenvironment composed primarily of different types of non-cancerous immune cells with a rare population (~1%) of tumor cells. Detailed characterization of these cellular components and their spatial relationship is crucial to understand crosstalk and therapeutic targeting in the cellular ecosystem of the tumor microenvironment (TME). METHODS: In this study, we performed high dimensional and spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 35 publications
6
56
0
Order By: Relevance
“…The TME of cHL possesses various innate immune cells such as macrophages and dendritic cells. 32,55 These cells also possess MHC-II expression and act as antigen-presenting cells, which may be involved in antitumor immunity. In addition, HRS cells have complementary mechanisms of immune evasion including alterations of NF-kB, JAK/STAT, PI3K signals, PD-L1, and B2M, all of which are crucial for immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…The TME of cHL possesses various innate immune cells such as macrophages and dendritic cells. 32,55 These cells also possess MHC-II expression and act as antigen-presenting cells, which may be involved in antitumor immunity. In addition, HRS cells have complementary mechanisms of immune evasion including alterations of NF-kB, JAK/STAT, PI3K signals, PD-L1, and B2M, all of which are crucial for immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the randomized phase 2 study of brentuximab vedotin and nivolumab with or without ipilimumab is ongoing (NCT01896999) to assess the efficacy of dual CTLA-4 and PD-1 blockade. LAG-3 might be a potential target considering the recent single-cell RNA sequence (scRNA-seq) analysis which showed that a subset of HL-associated T cells expressed high levels of this checkpoint molecule [ 74 ]. Alternatively, given that loss of MHC-II confers therapeutic resistance to HL, harnessing innate immunity might be a key approach.…”
Section: Clinical Response and Resistance To Immune Checkpoint Blockamentioning
confidence: 99%
“…In the study, increased LAG3 + T cells were shown to be in the direct vicinity of MHC class-II-deficient tumor cells. 73 Zhu et al investigated ovarian cancer patients using IMC to identify biomarkers of immunotherapy response. In the study, the authors found that the highest increase in CD8 + T cells and forkhead box protein P3 (FoxP3) + cells was found in patients responding to the combination of durvalumab and tremelimumab.…”
Section: Imaging Mass Cytometrymentioning
confidence: 99%